Energy Transitions Roundtable Proceedings - G. Kent Fellows; Ahmed Elmeligy; Katharina Koch; Robert Mansell; Dylan Rama; Ivana Skendrovic (The School of Public Policy Publications)
On February 21, 2024, the University of Calgary School of Public Policy convened a full day roundtable event discussing the topic of “Seizing Opportunities in the Energy Transition.” The condensed documentation and review provided here reflect the authors’ synthesis of the content and opinions expressed during the day’s events. As such, this interpretation is attributable to the authors and not to any of the named or unnamed speakers or audience members.